カイヨウ エイセイ シーサット ノ コウド ソクテイ データ ニ ヨル ナンキョク シュウヘン カイイキ ジオイド ノ ヒョウカ - 瀬川, 爾朗; セガワ, ジロウ; Segawa, Jiro (1982)
P(論文) NASAが打ち上げた海洋衛星シーサットのレーダー高度計による海面高の測定が, 1978年の6月から9月にかけて行われ, 機械精度±10cmという高精度の測定に成功した。このデータを処理することにより, 南緯45°から南極大陸の縁辺までの海面トポグラフィの図化を行った。衛星の軌道誤差が大きいため, その機械精度に反して, 海面高のデータには±5mの誤差が含まれることがわかった。しかし, ロス海やウェッデル海などの湾形の地帯でのジオイドの顕著なへこみや, 東南極沖合のインド洋におけるジオイドのもり上がりなどが, みごとに測られていることもわかった。 The SEASAT radar altimetry data, which were obtained during its operational period from June to September 1978,have been processed, and the sea surface topography and/or the geoid in the area between 45°S and the margin of the Antarctic Continent have been contour-mapped. Mainly because of the uncertainty involved in the satellite altitude the sea surface topography includes maximum errors of ±5m. However, some significant features such as geoid depressions at the Ross Sea and the Weddell Sea or the regional geoid upheavals over the Indian Ocean off East Antarctica have been clearly displayed. departmental bulletin paper